2023
DOI: 10.3390/hydrology10110210
|View full text |Cite
|
Sign up to set email alerts
|

Source Attribution of Atmospheric Dust Deposition to Utah Lake

Justin T. Telfer,
Mitchell M. Brown,
Gustavious P. Williams
et al.

Abstract: Atmospheric deposition (AD) is a significant source of nutrient loading to waterbodies around the world. However, the sources and loading rates are poorly understood for major waterbodies and even less understood for local waterbodies. Utah Lake is a eutrophic lake located in central Utah, USA, and has high-nutrient levels. Recent research has identified AD as a significant source of nutrient loading to the lake, though contributions from dust particles make up 10% of total AD. To better understand the dust AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…We estimate the mass of DP in Utah Lake to be between 10 and 50 t at any given time (Figure 19), with monthly mass changes that can be either positive or negative, increasing or decreasing by as much as 15 t (Figure 20). Current estimates for external TP loading, however, are between 18 and 35 t/month and are always positive [4][5][6][7][8]. We show that the monthly change in DP mass in Utah Lake is comparable in magnitude or exceeds the estimated total P load to the lake and that the differences in loading must be attributable to internal cycling caused by sediment-water interactions.…”
Section: Varabilitymentioning
confidence: 76%
See 1 more Smart Citation
“…We estimate the mass of DP in Utah Lake to be between 10 and 50 t at any given time (Figure 19), with monthly mass changes that can be either positive or negative, increasing or decreasing by as much as 15 t (Figure 20). Current estimates for external TP loading, however, are between 18 and 35 t/month and are always positive [4][5][6][7][8]. We show that the monthly change in DP mass in Utah Lake is comparable in magnitude or exceeds the estimated total P load to the lake and that the differences in loading must be attributable to internal cycling caused by sediment-water interactions.…”
Section: Varabilitymentioning
confidence: 76%
“…There are conflicting estimates for Utah Lake P loads. For example, AD studies performed by Brown et al [5], Barrus et al [6], Olsen et al [7], and Telfer et al [8] measured AD rates from 75 to 235 t of TP/year (approximately 2 to 7 times more AD mass than estimated by the ULWQS model). Other studies have shown that internal loading from lakebed sediments could contribute significantly to Utah Lake's P content.…”
Section: Introduction 1study Motivationmentioning
confidence: 99%